FORMULATION AND ANTIBACTERIAL ACTIVITY TEST OF ANTI-ACNE GEL FROM ETHANOL EXTRACT OF SENDUDUK LEAVES (Melastoma malabathricum. L) - Novelni, Ringga; Mimi Yupelimi; Dina Agustina; Diza Sartika; Vici Syahril Chairani (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Treatment of inflamed acne is done by administering antibiotics and chemicals, which can usually cause side effects such as skin irritation and resistance. To avoid this, it can be replaced by doing traditional treatment using natural ingredients. Senduduk plant (Melastoma malabathricum L.) is one of the natural ingredients that can be used to treat acne because it contains secondary metabolites of flavonoids, phenolics, tannins and terpenoids that are very potential as antibacterials. This study aims to determine the ethanol extract of senduduk leaves can be formulated in a physically stable gel dosage form and determine the antibacterial activity against Propionibacterium acne and Staphylococcus aureus bacteria. This study used an experimental method by making 3 types of formulas containing ethanol extract of senduduk leaves (Melastoma malabathricum L.) 1.5%, 2.5% and 3.5%. Furthermore, the evaluation of the gel preparation included organoleptic test, homogeneity test, pH test, spreadability test and adhesion test. Antibacterial activity testing was carried out by the pitting diffusion method using Klindamycin as a positive control. Based on the results of the gel preparation evaluation, it shows that the anti-acne gel preparation has physical quality that meets the standards. Antibacterial activity test of senduduk leaf ethanol extract gel against S.aureus bacteria at concentrations of 1.5%, 2.5% and 3.5% had inhibition zone diameters of 20.3 mm, 21.4 mm, and 24.2 mm, respectively, while against P. acnes bacteria it was 21.6 mm, 25.3 mm, and 26.5 mm. It can be concluded that the anti-acne gel of senduduk leaf ethanol extract has antibacterial activity against S. aureus and P. acnes bacteria and can be made into an anti-acne gel dosage form.